PEMBUATAN PEREKAT FENOLIK DARI LINDI HITAM YANG DIPEKATKAN DENGAN TANIN ATAU FENOL KRISTAL - R Sudradjat; G Pari; M I lskandar (Pusat Penelitian dan Pengembangan Hasil Hutan, 2003)
Phenol compounds in waste water of pulp and paper industry are toxic and harmful to environment. Phenol compounds are also an expensive chemical with wide range uses, such as raw materials for the manufacture of phenol formaldehyde glue.This experiment was aimed at looking into appropriate method to cope with the problems of black liquor's phenol by converting it to the most valuable glue largely and widely used in the plywood industries, i.e. phenol-formaldehyde. The experiment was divided into three stages, i.e. (a) recovery of phenol from black liquor after distillation; (b) selecting phenol compounds from another source as an additive to increase the existing phenol concentration in the distilled black liquor; and (c) working out optimum phenol concentration able to develop maximum bonding strength of the phenol-formaldehyde glue.Phenol compounds investigated as an additive to increase distilled phenol concentration are crystal phenol and tannin. The two additives were added in ratio of 1:3, 1:5 and 1:7 (crystal phenol/tannin to distilled phenol). After that, the mixture is reacted with formalin to form phenol formaldehyde glue following standard procedure. The phenol formaldehyde glue was applied to plywood and then was analyzed for moisture content, density and bonding strength.Results showed that phenol crystal addition is better than tannin due to lower in moisture, but higher in density and bonding strength. At all mixture ratio, tannin addition gave lower plywood bonding strength compare to standard (14 kg/cm2), but phenol addition gave higher plywood bonding strength (18-24 kg/cm2). Further experiment should be conducted to use crystal phenol as an additive to increase distilled phenol concentration.